Effect of circulating ceramides on adiposity and insulin resistance in patients with type 2 diabetes: An observational cross‐sectional study - Emmanuel K. Ofori; Alfred Buabeng; Seth D. Amanquah; Kwabena O. Danquah; Seth K. Amponsah; Wormenor Dziedzorm; Francis K. Dogodzi; Laurinda X. Adusu‐Donkor; Segla K. Bernard; Henry Asare‐Anane (Endocrinology, Diabetes & Metabolism, 2023)
Abstract Introduction Insulin resistance (IR) is one of the common chronic metabolic disorders in Africa and elsewhere. Accumulation of lipids in the body may be due to an imbalance in the metabolism of lipids, glucose and proteins. Ceramides are a sphingolipid class of lipids that are biologically active and vital in the production of more complex lipids. Circulating ceramides are thought to have a role in the development of obesity‐related IR, although the precise involvement remains unclear. Aim To investigate the impact of circulating ceramide on IR and body adiposity in people with and without type 2 diabetes mellitus (T2DM). Methodology The study was observational and cross‐sectional. There were a total of 84 volunteers with T2DM and 75 nondiabetics (control). The participants' ages, body mass indexes (BMI), waist circumferences, and blood pressure (BP) were among the clinical parameters assessed. Ceramide levels, fasting plasma glucose (FPG), lipids, basal insulin levels and glycated haemoglobin (HbA1c) were also measured. Additionally, the homeostatic model assessment for IR (HOMA‐IR) and beta cell function (HOMA‐β) were computed. Results T2DM and control participants had different mean values for anthropometric parameters, BP, FPG, HbA1c, lipids, insulin, HOMA‐IR, HOMA‐β and ceramide levels (p < .05 for all). HOMA‐IR, HOMA‐β and cardiovascular risk were significant correlates with ceramide levels in the T2DM group (r = 0.24; −0.34; 0.24, p < .05, respectively). Further, FPG (OR = 1.83, p = .01) and ceramide (OR = 1.05, p = .01) levels were significant predictors of IR in the case group. Conclusion Patients with T2DM exhibited high ceramide concentrations, which, when combined with high FPG, were associated with IR. The consequences of circulating ceramides in health and disease; however, merit further research.